Everyday life and Cross-Border Relations in Transcarpathia during the Khrushchev era - Natalia Varadi; Váradi Natália; Вароді Наталія (Видавничий дім «Гельветика», 2021)
Abstract. After the death of J. Stalin, in the period of the Khrushchev “thaw” (1953–1964) some positive changes were traced in the Soviet Union, as well as in Transcarpathia region, which was the “Western gate” of the USSR: fewer repressions, partial liberalization of political life, slight weakening of the totalitarian regime, lots of political, economic and social reforms. In Transcarpathia, the Soviet authorities did their utmost to ensure that the area was fully integrated into the Soviet system. During the implementation of planned economy, quantity prevailed over quality. During the Khrushchev era, the main goals of the Transcarpathian political leadership were among others eliminating but at least reducing unemployment, improving the trade, establishing and deepening friendly relations and co-operation with neighbouring countries, developing tourism and infrastructure, reducing housing shortages, developing urban industries, which entailed the acceleration of urbanization processes etc. The food and light industry started to develop. The milling industry also developed, as the Soviet troops stationed in Central Europe were supplied from Transcarpathia. The period from 1953 to 1964 were years of great reorganization and failure in the Soviet Union. It became increasingly clear that Khrushchev’s reforms would not realize the hopes to improve the economy and to raise the standard of living of society. Generally, Khrushchev’s policy was inconsistent and debatable. In addition, the secretary-general surrounded himself with toadies, so poorly selected his advisers, blindly trusted them, which had increasingly serious consequences and caused his fall. The Presidium of the Communist Party at the October Congress of the Central Committee of the Communist Party of the USSR, in 1964 dismissed N. Khrushchev.

Резюме. Після смерті Й. Сталіна в період хрущовської «відлиги» (1953–1964) простежуються деякі позитивні зміни в Радянському Союзі, а також у Закарпатській області, яка була «Західною брамою» СРСР: менш інтенсивні репресії, часткова лібералізація політичного життя, незначне послаблення тоталітарного режиму, безліч політичних, економічних і соціальних реформ. На Закарпатті радянська влада зробила все від неї залежне, щоб ця територія була повністю інтегрована у радянську систему. Під час реалізації планової економіки кількість переважала над якістю. За часів епохи Хрущова основними цілями політичного керівництва Закарпаття були, зокрема, ліквідація, принаймні зменшення рівня безробіття, пожвавлення торгівлі, встановлення та поглиблення дружніх відносин і співпраці із сусідніми країнами, розвиток туризму й інфраструктури, вирішення проблеми з дефіцитом житла, розвиток міської промисловості, що сприяло прискоренню урбанізації, тощо. Почали розвиватися харчова та легка промисловість. Удосконалювалася і фрезерна промисловість, оскільки радянські війська, дислоковані у Центральній Європі, отримували постачання із Закарпаття. Період із 1953 по 1964 р. був часом великої реорганізації та невдач у Радянському Союзі. Ставало дедалі зрозумілішим, що хрущовські реформи не допомагають утілитися надіям на поліпшення економіки та підвищення рівня життя суспільства. Загалом політика Хрущова була непослідовною та дискусійною. Окрім того, генеральний секретар оточував себе недоброзичливцями, так хибно відбирав своїх радників, сліпо довіряв їм, що це мало все більш серйозні наслідки та призвело до його падіння. Президія Комуністичної партії на Жовтневому з’їзді ЦК Компартії Радянського Союзу 1964 р. звільнила М. Хрущова.
Повсякденне життя й транскордонні відносини на Закарпатті протягом періоду Хрущова
Keywords: Transcarpathia during 1953–1964; border; USSR; Hungarian People’s Republic; cooperation